Selectivity of Drift Gill Net in Fishing Port Nusantara Sungailiat of Bangka Belitung Province - Isnaniah Isnaniah; Pareng Rengi; Bustari Bustari; Ayu Nita Ervina Tambunan (Fakultas Perikanan dan Kelautan, Universitas Riau, 2022)
Selectivity of fishing gear is defined as the ability of fishing gear to achieve certain fishing targets according to type and size during the fishing process and allows all unwanted bycatch to be released without injury. The purpose of this study was to determine the selectivity of mesh size and composition of drift gill net in PPN Sungailiat. The result of this research is that the drift gill net with mesh size of 8.89 cm catches tuna with a fork length range of 32 – 45.7 cm and the highest catching ratio is found in the fork length (L) = 37.7 cm with Sa = 0.999289326. Meanwhile, the mesh size of 10.16 cm caught fish that had a fork length range of 36.6 – 50.3 cm and the highest catch ratio was for the fork length (L) = 43.3 cm with Sb = 0.999974108. So that the drift gill nets with mesh size 10.16 cm are more selective than drift gill nets with a mesh size of 8.89 cm, because the L value is larger and the S value is closer to 1. As well as catching more large fish that deserve to be caught (≥ 40 cm).